Proposta de instrução de trabalho de fiscalização para tratamento de desvio da qualidade de insumos farmacêuticos ativos: com base no caso das “Sartanas” - Domingos, Janaina Lopes (2020)
One of the elements of the Brazilian Health Regulatory Agency – Anvisa is to “promote the protection of the population’s health by executing sanitary control of the productions marketing and use of products and services subject to health regulation”, therefore the monitoring of failures or problems caused by a medicine is an essential element of a health surveillance system. Recently, a series of international warnings related to the presence of potentially carcinogenic N-nitrosamine class impurities in active pharmaceutical ingredients – API – angiotensin II receptor antagonist antihypertensive, have forced all over the world agencies to undertake a great amount of enforcement measures in a relatively short time. The study’s objectives were to describe the history of inspection actions performed by Anvisa in the case., to describe the impurities’ genesis and toxicity, and describe the structure and tools of the inspection of APIs, discuss Anvisa’s performance int international scenario. Based on the obtained data, a Working Instruction was written for the Anvisa’s Coordination of API Inspection for the treatment of recurrent alerts regarding deviations int the API’s quality, in order to make sanitary inspection actions more effective, prompt and anticipatory as the leading international health authorities.